Cicero, the beginnings of eloquence in Rome and the studium di(s)cendi (de orat. 1, 13-16) - Boldrer, Francesca (Ciceroniana On Line, 2024)
The article examines Cicero’s excursus on the beginnings of eloquence in Rome in the preface to the first book of De oratore (1, 13-16). The analysis highlights both positive and critical aspects in the studium of young Romans (among whom Cicero includes traces of his own autobiography). This studium as outlined by Cicero privileges a practical over a theoretical approach and is marked by the lack of a cultural component. Cicero, however, argues for the importance of such an ingredient to achieve excellence. Ultimately, the discussion has a bearing also on textual issues characterising the passage, specifically on the controversial use of either dicendi or discendi (studium) in de orat. 1, 14.